Circulating NK‐Cell Subsets in Renal Allograft Recipients With Anti‐HLA Donor‐Specific Antibodies. Issue 3 (5th February 2015) - Crespo, M.; Yelamos, J.; Redondo, D.; Muntasell, A.; Perez‐Saéz, M. J.; López‐Montañés, M.; García, C.; Torio, A.; Mir, M.; Hernández, J. J.; López‐Botet, M.; Pascual, J.
<x xml:space="preserve">Abstract</x> Detection of posttransplant donor‐specific anti‐HLA antibodies (DSA) constitutes a risk factor for kidney allograft loss. Together with complement activation, NK‐cell antibody‐dependent cell mediated cytotoxicity (ADCC) has been proposed to contribute to the microvascular damage associated to humoral rejection. In the present observational exploratory study, we have tried to find a relationship of circulating donor‐specific and nondonor‐specific anti‐HLA antibodies (DSA and HLA non‐DSA) with peripheral blood NK‐cell subsets and clinical features in 393 renal allograft recipients. Multivariate analysis indicated that retransplantation and pretransplant sensitization were associated with detection of posttransplant DSA. Recipient female gender, DR mismatch and acute rejection were significantly associated with posttransplant DSA compared to HLA non‐DSA. In contrast with patients without detectable anti‐HLA antibodies, DSA and HLA non‐DSA patients displayed lower proportions of NK‐cells, associated with increased CD56bright and NKG2A+ subsets, the latter being more marked in DSA cases. These differences appeared unrelated to retransplantation, previous acute rejection or immunosuppressive therapy. Although preliminary and observational in nature, our results suggest that the assessment of the NK‐cell immunophenotype may contribute to define signatures of alloreactive humoral responses in renal allograft recipients.